Tail gas enhanced solid waste-based building material aggregate and preparation method thereof
Patent Information
- Application Number
- CN202611345309.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]为克服现有技术中CO2捕集与NOx脱除各自独立运行、缺乏协同净化方案,以及固废活化方法(酸处理、高温焙烧)存在二次污染和破坏胶凝性能等问题,本发明提供一种尾气增强型固废基建材骨料的制备方法,以钢渣、镁渣为原料,经双级高磨、生物炭掺杂后造粒并水合活化,再利用等离子体表面处理后进行含CO2-NOx的工业烟气处理,将惰性工业固废转化为兼具CO2矿化与NOx催化还原双功能的活性材料,实现在100-200°C低温条件下烟气中CO2和NOx的高效协同净化,且制备得到的骨料得以增强处理,可作为建材骨料实现资源化利用
1. 等离子体能量利用效率的突破性提升。通过步骤3)中导电生物炭形成的微电极阵列,在DBD电场中产生局域场增强效应,使得等离子体活性物种的产率和空间分布密度高于传统纯气相DBD处理固体材料的方式,从根本上解决了等离子体处理大量颗粒材料时能量利用率低的技术瓶颈。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the fields of building material preparation and industrial exhaust gas treatment technology, and in particular to an exhaust gas-enhanced solid waste-based building material aggregate and its preparation method. Background Technology
[0002] Flue gas emitted from industrial processes such as cement, steel, and coal-fired power generation contains large amounts of both carbon dioxide (CO2) and nitrogen oxides (NOx). x CO2 and NOx emissions from industrial flue gas are major sources of the greenhouse effect and air pollution. With increasingly stringent environmental standards, reducing CO2 emissions from industrial flue gas and NOx emissions is becoming increasingly important. x Ultra-low emissions have become a common technological challenge that urgently needs to be addressed. However, most existing technological systems target the treatment of single pollutants separately—CO2 capture and NO2 capture. x Separating these components from their independent operation leads to system complexity and increased investment and operating costs. Therefore, it is necessary to develop a system capable of simultaneously processing CO2 and NO. x The synergistic purification technology has significant economic and environmental value.
[0003] In CO2 capture, chemical absorption methods (such as the amine method) are currently the most mature industrialized technology. This method utilizes an organic amine solution (such as monoethanolamine MEA) to undergo a reversible chemical reaction with CO2, absorbing it at low temperatures and desorbing it at high temperatures to achieve CO2 separation and concentration. However, chemical absorption methods have inherent drawbacks: first, the energy consumption for absorbent regeneration is extremely high (typically 2.5-4.0 GJ / t CO2), resulting in high capture costs; second, organic amine solutions are prone to oxidative and thermal degradation during operation, producing corrosive byproducts that severely corrode equipment; and third, the emission of degradation products and volatile amines poses new environmental risks. These problems make the promotion of chemical absorption methods in non-power industries such as steel and cement face significant economic and technical obstacles.
[0004] In NO x In terms of pollution control, selective catalytic reduction (SCR) technology is currently the mainstream process. This technology uses V₂O₅-WO₃ / TiO₂ or Fe-based and Cu-based molecular sieves as catalysts, and utilizes NH₃ to reduce NO₂ within a high-temperature window of 300-400°C. x It is reduced to N2. However, SCR technology faces three prominent problems: First, the high-temperature operating window means that the flue gas needs to be reheated or must be placed in a high-dust, high-sulfur area before the economizer, leading to increased risks of catalyst wear, blockage, and SO2 poisoning; second, vanadium-tungsten-titanium catalysts are expensive, and spent catalysts are hazardous waste with high disposal costs; third, SCR technology only targets NO. xThe single-pollutant design does not involve CO2 reduction at all. Even if CO2 chemical absorption is combined with SCR denitrification in series, not only will the investment and operating costs increase exponentially, but the operating temperature windows of the two (40-60°C absorption / 100-120°C regeneration vs 300-400°C SCR) are completely mismatched, making system integration very difficult.
[0005] In terms of solid waste resource utilization, metallurgical solid wastes such as steel slag and magnesium slag are rich in CaO, MgO, and transition metal oxides such as Fe and Mn. Theoretically, they possess both CO2 mineralization reactivity and catalytic activity, and have the potential to prepare low-cost purification materials. Ma et al. (Int J Greenhouse Gas Control, 2021) studied the synergistic CO2 mineralization of steel slag coupled with calcium carbide slag, confirming that Ca2SiO4 and Ca3SiO5 in steel slag can react with CO2 to generate CaCO3. Liu et al. (Constr Build Mater, 2021) used CO2 to treat steel slag to improve its cementing activity, verifying the effect of carbonation on improving the microstructure of the material. However, the above works only focus on the single function of CO2 mineralization, and unactivated steel slag has a low specific surface area (usually <5m²). 2 / kg), lack of surface active sites, slow mineralization reaction rate, and no ability to target NO. x The catalytic reduction capacity. To improve the activity of solid waste, existing methods mainly rely on acid treatment (such as impregnation with hydrochloric acid and acetic acid) or high-temperature roasting (600-900℃). However, these methods have serious secondary pollution (acidic waste liquid) and high energy consumption problems, and will irreversibly destroy the gelling activity of the material - which is precisely the basis for the post-use material to be used as a building material.
[0006] Furthermore, research indicates that CO2 can carbonize calcium hydroxide in cement-based materials, thereby increasing the strength of cement-based products. Existing technologies utilize CO2 for carbonization curing of building materials or use the carbonized product as a cementitious material, but eliminating NO... x However, there are no mature methods for the resource utilization of the industrial solid waste generated later.
[0007] In summary, existing technologies share the following common shortcomings: First, CO2 capture and NO... x First, there is a lack of synergistic purification materials and technologies capable of simultaneously treating two pollutants, as each operates independently. Second, while solid wastes such as steel slag are rich in active components, existing activation methods (acid treatment, high-temperature roasting) suffer from serious secondary pollution, high energy consumption, and damage to the cementitious properties of materials, making it difficult to achieve a complete green utilization chain of "activation-purification-building materialization." Third, traditional SCR denitrification requires temperatures above 300℃, while chemical absorption CO2 capture operates at low temperatures; the temperature windows of the two are completely incompatible, leading to difficulties in system integration. Fourth, the removal of CO2 and NO...x The resulting solid waste was not utilized for high-value resource recovery. Therefore, there is an urgent need to develop a green, low-temperature method that can simultaneously mineralize CO2 and NO in solid waste. x A dual-function activation method of catalytic reduction is proposed and organically integrated with the material preparation process to achieve synergistic purification of multiple pollutants in flue gas and high-value utilization of solid waste. Summary of the Invention
[0008] To overcome the limitations of existing technologies in CO2 capture and NO... x To address the issues of independent operation, lack of synergistic purification solutions, and secondary pollution and damage to gelling properties associated with solid waste activation methods (acid treatment, high-temperature roasting), this invention provides a method for preparing tail gas-enhanced solid waste-based building material aggregates. Using steel slag and magnesium slag as raw materials, the aggregates undergo two-stage high-speed grinding, biochar doping, granulation, and hydration activation. Following plasma surface treatment, the aggregates are then subjected to CO2-NO3-containing processes. x Industrial flue gas treatment transforms inert industrial solid waste into a product that combines CO2 mineralization and NO2 oxidation. x A dual-function active material for catalytic reduction can achieve the reduction of CO2 and NO in flue gas at low temperatures of 100-200°C. x The efficient and synergistic purification process enhances the aggregates produced, enabling them to be used as building material aggregates for resource utilization.
[0009] Specifically, the preparation method of the exhaust gas-enhanced solid waste-based building material aggregate of the present invention includes the following steps: 1) Weigh each ingredient according to its weight. 2) Mix 100 parts of steel slag and 50-100 parts of magnesium slag evenly, perform initial grinding, add 2-4 parts of stearic acid or anhydrous ethanol, and finely grind to obtain active micro powder. 3) Add 1-10 parts of biochar to the activated micro powder, mix with water until homogeneous, granulate, and cure to obtain green body granules. 4) The green body particles are placed in a dielectric barrier discharge plasma reactor and subjected to plasma surface treatment in a non-oxidizing atmosphere to obtain purified aggregate. 5) Place the purified aggregate in a container containing CO2-NO2. x It is obtained by treating industrial flue gas.
[0010] This invention employs a two-stage high-speed ball mill, with the addition of stearic acid or anhydrous ethanol as a process control agent, particularly in the fine grinding stage. This helps to suppress the cold welding and agglomeration of ultrafine powders, ensuring that the ball milling energy is primarily used for continuous particle refinement rather than repeated welding. The calcium silicate and calcium aluminate minerals in the steel slag provide a cementing framework and Fe / Mn catalytic elements, while the MgO in the magnesium slag provides a CO2 mineralization active phase and can be further processed by Mg… 2+Leaching regulates the crystal structure of subsequent mineralization products. Studies have shown that the two-stage high-speed ball milling method of this invention significantly increases the specific surface area and surface defect density of solid waste powder through high-energy impact and shearing, providing abundant reaction interfaces for subsequent steps. The significant increase in specific surface area directly increases the reaction efficiency with CO2 and NO. x The effective contact area is the basis for improving the mineralization rate and catalytic conversion rate.
[0011] The addition of biochar in this invention plays a triple role in the material: (i) as a microelectrode array in the DBD electric field of step 4) to enhance plasma energy efficiency and active species yield; (ii) utilizing its intrinsic carbothermal reduction activity (2NO+C→N2+CO2) and the SCR catalytic function of its surface oxygen-containing functional groups (-COOH, -OH, C=O) to directly participate in NO reduction. x The chemical reduction of the material constitutes an independent contributing pathway to its denitrification capability; (iii) through the transfer of electrons between the carbon-based π electrons and Fe sites (Fe 3+ +C (reduced state) → Fe 2+ +C=O), acting as a solid reducing agent during the reaction, continuously reducing Fe 3+ Reduced to catalytically active Fe 2+ This slows down the decay of catalyst activity.
[0012] Preferably, in step 2), the initial grinding is ball milling at 300-500 rpm for 30-60 min until D50 ≤ 20 μm.
[0013] Preferably, in step 2), the fine grinding is performed by ball milling at 400-700 rpm for 60-180 min, resulting in an active micro powder with a specific surface area of 500-1500 m². 2 / kg.
[0014] Preferably, the biochar in step 3) is prepared by anaerobic pyrolysis of biomass raw materials at 300-600℃, with a particle size ≤50μm.
[0015] Preferably, the biochar is at least one of corn cob, straw, sawdust, or rice husk.
[0016] Preferably, in step 3), the curing process involves hydration curing at a temperature of 60-100℃ and a relative humidity of ≥90% for 12-48 hours. In this invention, hydration curing after granulation produces hydrated calcium silicate gel (CSH) and calcium hydroxide. The CSH gel possesses an ultra-high specific surface area and a layered structure, making it an excellent carrier for CO2 mineralization reactions; Ca(OH)2 provides a high concentration of reactive Ca... 2+ The hydration activation process is also a fundamental reaction for the strength development of cementitious materials, and it is completely harmless to the material's subsequent application in building materials.
[0017] Preferably, in step 3), the particle size of the green body is 0.5-10 mm.
[0018] Preferably, in step 4), the processing power is 100-500 W, the processing time is 5-30 min, the discharge frequency is 5-20 kHz, and the discharge gap is 2-10 mm.
[0019] Preferably, the non-oxidizing atmosphere in step 4) is argon, nitrogen, or a mixture thereof.
[0020] This invention also relates to exhaust gas-enhanced solid waste-based building material aggregates, specifically, those prepared by the above-described preparation method.
[0021] This invention also relates to the application of the above-mentioned exhaust gas-enhanced solid waste-based building material aggregate in the preparation of cement-based building materials.
[0022] The core inventive point of this invention is: First, the biochar microelectrode array enhances the plasma effect. The conductive biochar particles incorporated in step 3) form a distributed microelectrode array in the DBD electric field of step 4). Due to the high conductivity of biochar (10⁻⁶ ppm), the microelectrode array enhances the plasma effect. -1 -10 1 S / cm) is much higher than that of solid waste matrix (<10). -6 Each biochar particle acts as a local electric field enhancement point, with the electric field strength near its tip and surface being 1-3 orders of magnitude higher than the background electric field. This effect brings two benefits: (i) it reduces the effective breakdown voltage, enabling stable ignition of the discharge at lower power inputs; and (ii) it generates a high density of electrons, excited-state molecules, and active free radicals around each biochar particle, resulting in higher plasma energy utilization efficiency and active species yield than the traditional mode of pure gas-phase DBD treatment of solid materials.
[0023] Second, quantitative control of plasma dose-defect density-catalytic performance. In step 4), the plasma dose D (D = P × t, i.e., the product of processing power and processing time) is used as a unified control parameter. By changing the value of D, the oxygen vacancy concentration on the material surface (quantitatively characterized by the relative area of the oxygen vacancy characteristic peak at 531.0-531.5 eV in the O1s spectrum of X-ray photoelectron spectroscopy) and Fe... 2+ / Fe 3+ The molar ratio was quantitatively characterized by peak fitting of the XPS Fe 2p3 / 2 spectrum. In particular, when the D value is in the range of 3000-15000 W•min, the surface oxygen vacancy concentration can reach over 15%. 2+ / Fe 3+ The optimal molar ratio is controlled within the range of 0.3-1.2, at which point the material exhibits the best response to NO. xThe catalytic reduction performance reaches its optimal level.
[0024] Third, CO2 mineralization sites and NO x Spatial separation of catalytic sites. High-energy electrons and ions from the plasma primarily act on the outer surface of the material (penetration depth typically on the nanometer to submicrometer scale), selectively creating oxygen vacancies on the Fe / Mn oxide surface and reducing Fe. 3+ →Fe 2+ NO x The active centers for catalytic reduction. In step 3), the CSH gel and Ca(OH)2 generated during hydration activation are mainly distributed within the internal channels and bulk phase of the material particles, naturally shielded by the surface layer and unaffected by plasma etching. Therefore, the mineralization active sites (Ca / Mg-based) and the catalytic active sites (Fe-Ov) are spatially separated and chemically independent: CO2 reacts with Ca(OH)2 and CSH in the channels to undergo carbonation, while NO... x Fe on the outer surface 2+ Catalytic reduction occurs at the -Ov site. The two types of reactions achieve true synergy rather than simple superposition.
[0025] Fourth, the chemical coupling cycle of mineralization driven by SCR water production. For every 1 mol of NO converted by SCR catalytic reduction, 1.5 mol of H2O is generated (4NO + 4NH3 + O2 → 4N2 + 6H2O). These water molecules diffuse into the material pores in a gaseous state at an operating temperature of 100-200°C, undergoing an in-situ hydration reaction with free CaO in the steel slag / magnesium slag (CaO + H2O → Ca(OH)2, ΔH° = -65 kJ / mol). The generated Ca(OH)2 then undergoes a carbonation reaction with CO2 in the flue gas (Ca(OH)2 + CO2 → CaCO3 + H2O, ΔH° = -113 kJ / mol), and the water molecules are released back into the gas phase. Thus, the water produced by the SCR reaction constitutes the chemical mediator of the CaO → Ca(OH)2 → CaCO3 mineralization pathway—water circulates between SCR and mineralization, without being consumed but continuously driving the mineralization reaction. The significance of this coupling mechanism lies in the fact that, under temperature conditions of 100-200°C, the direct gas-solid carbonation of CaO (CaO + CO2 → CaCO3) is controlled by solid-phase diffusion and has an extremely low rate; while through the indirect pathway mediated by H2O (CaO → Ca(OH)2 → CaCO3), the reaction rate is increased by 1-2 orders of magnitude. SCR provides "activating water" for mineralization, and the regenerated water after mineralization consumes CO2 is returned to the SCR side. The two achieve true chemical coupling at the material flow (H2O) level, rather than a simple functional superposition.
[0026] Fifth, the exhaust gas is used to enhance the particles, achieving the grade required for building material aggregates. The resulting green body particles are less susceptible to CO2-NO2 content. x It is processed in industrial flue gas, which not only purifies the exhaust gas, but also strengthens the particles to achieve the strength of solid waste-based building material aggregates, which can be used in the production of cement-based building materials.
[0027] This invention has the following technical advantages: 1. Breakthrough improvement in plasma energy utilization efficiency. Through the microelectrode array formed by conductive biochar in step 3), a local field enhancement effect is generated in the DBD electric field, which makes the yield and spatial distribution density of plasma active species higher than that of traditional pure gas phase DBD treatment of solid materials, fundamentally solving the technical bottleneck of low energy utilization when plasma treats a large number of particulate materials.
[0028] 2. Quantitative controllability of defect density and catalytic performance. Using plasma dose D = P×t as a unified control parameter, a model was established to determine the relationship between D and oxygen vacancy concentration and Fe. 2+ / Fe 3+ The quantitative relationship between ratio and NOx catalytic performance upgrades material performance from "experience-based trial and error" to "predictable design," ensuring the repeatability of the preparation process and the consistency of product quality.
[0029] 3. Synergistic effect of CO2 mineralization and NOx catalytic reduction via a dual pathway. On one hand, plasma selectively acts on Fe / Mn sites on the outer surface to create catalytic active centers without affecting the Ca / Mg mineralization sites generated by hydration activation in the internal channels, achieving spatial separation of the two types of active sites. On the other hand, water produced by the SCR reaction drives the mineralization cycle through the CaO→Ca(OH)2→CaCO3 pathway, while the water regenerated from mineralization re-participates in CaO hydration. Water molecules act as chemical messengers between the two functions, increasing the CO2 mineralization rate by approximately 10-30% under SCR synergistic operation compared to mineralization alone.
[0030] 4. Multifunctional Integration of Biochar. Biochar simultaneously serves multiple functions within the material, including microelectrode array-enhanced plasma, direct carbothermic denitrification (2NO + C → N2 + CO2), SCR catalysis via oxygen-containing functional groups on the carbon surface, and maintaining Fe through carbon-Fe electron transfer. 2+ The reduced state solid reducing agent has four functions, redefining carbon materials, which are traditionally regarded as merely adsorbents, as an independent contributing pathway to the denitrification capacity of materials.
[0031] 5. Entirely green and low-energy-consumption process. The entire preparation process requires no high-temperature roasting (traditional activation requires 600-900°C) and no acid-base treatment (traditional activation produces acidic waste liquid). The highest operating temperature is 60-100°C for hydration activation and the low-temperature plasma environment for plasma treatment, resulting in overall energy consumption far lower than traditional activation methods. Furthermore, it uses industrial solid waste such as steel slag and magnesium slag as the main raw materials, resulting in extremely low raw material costs and representing a resource-based utilization of solid waste.
[0032] 6. Zero-waste utilization throughout the entire material lifecycle. After use, the co-purification materials become mainly mineralized products containing CaCO3 and retain residual cementitious activity. They can be directly used as admixtures or aggregates in building material production without secondary treatment, forming a closed-loop resource utilization path of "solid waste → purification materials → building materials". Detailed Implementation
[0033] To characterize the technical effects of this invention, the preparation method of this invention was implemented and technical testing was conducted. During the experiment, the biochar preparation method was as follows: corn cobs were pyrolyzed in a tube furnace at 500°C for 2 hours under N2 atmosphere to prepare biochar. The biochar was then ground and passed through a 325-mesh sieve. The carbon content of this biochar was 78 wt%, the ash content was 8 wt%, and the electrical conductivity (compacted powder using the four-probe method) was approximately 5 × 10⁻⁶. -1 S / cm.
[0034] Material characterization methods involved: X-ray diffraction (XRD) was performed using a Cu Kα radiation source (λ=1.5406 Å), with a scanning range of 5-80° 2θ and a step size of 0.02°; the N2 adsorption-desorption specific surface area (BET) was measured at 77 K, and the sample was pre-degassed under vacuum at 150°C for 4 h; X-ray photoelectron spectroscopy (XPS) was performed using an Al Kα excitation source (1486.6 eV), with the binding energy calibrated at C1s 284.8 eV. The O1s spectrum peaks were divided into three components: lattice oxygen (529.5-530.0 eV), oxygen vacancies (531.0-531.5 eV), and surface hydroxyl / adsorbed oxygen (532.0-532.5 eV). Fe2p 3 / 2 After peak fitting, Fe 2+ (709.5-710.5 eV) and Fe 3+ Calculation of Fe peak area ratio (711.0-712.5 eV) 2+ / Fe 3+ Mole ratio.
[0035] CO2 mineralization efficiency and NO xThe catalytic removal performance was evaluated using a fixed-bed flow reactor: material loading was 20 g; the simulated flue gas composition was 15 vol% CO2, 500 ppm NO, 500 ppm NH3, 5 vol% O2, and N2 equilibrium; the total flow rate was 500 mL / min; and the reaction temperature was 150°C. Inlet and outlet gas compositions were monitored using a flue gas analyzer. CO2 mineralization efficiency was calculated based on the inlet and outlet CO2 concentration difference; NO... x Removal efficiency and N2 selectivity according to NO x The mass conservation calculations were performed to deduct the interference from N2O byproducts.
[0036] Example 1 A method for preparing exhaust gas-enhanced solid waste-based building material aggregates includes the following steps: 1) Weigh each ingredient according to its weight. 2) Mix 100 parts steel slag and 60 parts magnesium slag evenly, and perform initial grinding at 400 rpm for 45 min until the material D50 is reduced to about 18 μm. Add 2 parts stearic acid and finely grind at 550 rpm for 120 min to obtain active micro powder with a specific surface area of about 980 m². 2 / kg, D50 is approximately 6μm. 3) Add 5 parts biochar to the activated micro powder, mix thoroughly with water at a water-to-solid ratio of 0.25, granulate, and cure at 80℃ and 95% relative humidity for 24 hours to obtain 0.5-10 mm green body particles. 4) The green body particles were evenly spread on the quartz dielectric plate of the DBD flat plate reactor (discharge gap 5 mm). After purging with high-purity Ar (flow rate 200 mL / min) for 10 min, the high-frequency power supply was turned on for plasma treatment. The treatment parameters were: power 300 W, treatment time 15 min (plasma dose D = 4500 W•min), discharge frequency 10 kHz, to obtain purified aggregate. 5) The purified aggregate is loaded into the reactor, and simulated flue gas (composition: 15 vol% CO2, 500 ppm NO, 500 ppm NH3, 5 vol% O2, N2 balance) is introduced at a total flow rate of 500 mL / min and a space velocity (GHSV) of approximately 15000 h⁻¹. -1 The reaction temperature is 150°C.
[0037] The outlet gas was analyzed by a flue gas analyzer, and the CO2 mineralization efficiency was 68%, NO... xThe removal efficiency was 82%, and the N2 selectivity was 86%. 5-10 mm purified aggregate was screened and used to absorb simulated flue gas. The cylinder compressive strength before and after absorbing simulated flue gas was tested and found to be 5.2 MPa and 8.6 MPa, respectively. It can be seen that the purified aggregate has a good exhaust gas purification effect, and the exhaust gas has a reinforcing effect on the purified aggregate. The resulting exhaust gas-reinforced solid waste-based building material aggregate has good compressive strength.
[0038] Experimental Differentiation of Biochar Denitrification Contribution: To differentiate the independent denitrification contribution of biochar, a pure biochar control sample (only biochar underwent step 4) was prepared under the same DBD conditions (without solid waste components). Under the same fixed-bed conditions (150°C, simulated flue gas), the NO conversion rate of pure plasma-activated biochar was 28% (of which carbothermal reduction contributed approximately 18% and carbon surface functional group SCR catalysis contributed approximately 10%). Therefore, it is estimated that in the 82% total denitrification efficiency of Example 1, the biochar pathway (carbothermal reduction + carbon SCR + carbon-Fe synergy) contributes approximately 30-35 percentage points, and Fe... 2+ The catalytic SCR contribution from the -Ov site is approximately 35-40 percentage points, while non-catalytic pathways such as NH3 surface adsorption-reaction contribute approximately 10-15 percentage points. The three pathways are superimposed and complementary, ensuring the robustness of the material's overall denitrification capacity. Even if one pathway weakens due to fluctuations in operating conditions, the remaining pathways can still maintain a basic level of NO reduction. x Purification function.
[0039] SCR Permeate-Driven Mineralization Validation: To verify the promoting effect of SCR permeate on CO2 mineralization, two comparative experiments were set up: Group A was introduced with standard simulated flue gas (containing NO + NH3, SCR operated and produced water); Group B was introduced with alternative flue gas (NO + NH3 replaced by an equal amount of N2, SCR not operated, no water produced). CO2 concentration and other conditions were completely identical in both groups. After 2 hours of operation, the CO2 mineralization efficiency of Group A was 68%, while that of Group B was only 48%, a 20 percentage point increase during SCR operation. When an additional amount of steam equivalent to the SCR permeate (approximately 1500 ppm H2O) was introduced into Group B, the mineralization efficiency recovered to 64%, confirming that the H2O produced by the SCR was the direct cause of the enhanced mineralization, rather than other indirect effects of the SCR chemical reaction.
[0040] In contrast, without stearic acid in step 2), ball milling under the same conditions only achieved 420 m. 2 / kg.
[0041] Example 2 This embodiment maintains all other conditions identical to Example 1, except for the plasma treatment time in step 4), to demonstrate the quantitative regulatory effect of plasma dose D on the microstructure and catalytic performance of the material. Three treatment time gradients were set: 5 min (D = 1500 W•min), 15 min (D = 4500 W•min, same as Example 1), and 30 min (D = 9000 W•min). The XPS characterization and performance test results of each group of materials are summarized below:
[0042] The results showed that as the plasma dose D increased from 1500 to 4500 W•min, the oxygen vacancy concentration increased from 8.5% to 18.8%, and the Fe... 2+ / Fe 3+ The molar ratio increased from 0.18 to 0.68, NO x The removal efficiency increased from 55% to 82%, and the N2 selectivity also increased from 73% to 86%, indicating that oxygen vacancies and Fe... 2+ Together, they constitute the catalytic active center. When D further increases to 9000 W•min, the oxygen vacancy concentration continues to rise to 22.8%, but NO... x The removal efficiency dropped to 78%, and the N2 selectivity decreased to 81%. This indicates that excessively high plasma doses may lead to surface over-reduction, generating over-reduced Fe with higher N2O selectivity. 0 The species exhibits an optimal dosage window (D≈4500 W•min). The CO2 mineralization efficiency varies little across the three dosages (60-68%), verifying the relative independence between the CO2 mineralization active sites (Ca / Mg-based) and the plasma treatment intensity, consistent with the spatial separation mechanism.
[0043] Comparative Example 1 This comparative example only performs steps 1) to 3), omitting the plasma treatment in step 4), to demonstrate the effect of plasma activation on the NO imparting material. x The necessity of catalytic function. The obtained particles were evaluated under the same fixed-bed conditions: CO2 mineralization efficiency was 48% (proving that the untreated material still possesses some mineralization ability, derived from Ca(OH)2 and CSH generated by hydration activation), but NOx removal efficiency was only 12%, and N2 selectivity was only 35%. XPS analysis showed that the surface oxygen vacancy concentration of this material was only 3.5%, and Fe... 2+ / Fe 3+ The molar ratio is 0.05. This indicates that without plasma treatment, the material surface has almost no oxygen vacancy defects and low-valence Fe active centers required for catalysis. This comparative example clearly demonstrates that the plasma treatment in step 4) imparts NO to the material. xAn indispensable key step in the catalytic reduction function.
[0044] Comparative Example 2 This comparative example skips step 2), i.e., does not add biochar, and the remaining steps are completely consistent with Example 1, to demonstrate the enhancing effect of the biochar microelectrode array on plasma treatment and the independent denitrification contribution of biochar. Under the same DBD conditions in step 4), the effective discharge power of Comparative Example 2 is 188 W (300 W in Example 1), and the Lissajous pattern area is significantly reduced. Performance evaluation results are as follows: CO2 mineralization efficiency is 64% (close to Example 1), NO... x The removal efficiency was only 56% (a decrease of 26 percentage points compared to Example 1), and the N2 selectivity was 76%. Without biochar, denitrification relied solely on Fe. 2+ The catalytic SCR and NH3 surface reactions at the -Ov site lack the independent contribution pathways of carbothermic reduction and carbon SCR. XPS analysis showed that the oxygen vacancy concentration in Comparative Example 2 was 11.2%, and Fe... 2+ / Fe 3+ The molar ratio was 0.30, both lower than that of Example 1 containing biochar (18.8%, 0.68). These results validate the multiple key roles of biochar: (i) the microelectrode array effect, enhancing effective discharge power; (ii) the independent denitrification contributions of carbothermal reduction and carbon surface SCR catalysis (a 26 percentage point difference in denitrification efficiency); and (iii) the carbon-Fe electron transfer effect, maintaining a higher proportion of catalytically active Fe. 2+ Without biochar, the discharge is mainly limited to the macroscopic channels between the electrodes, which significantly weakens the activation effect on the surface of dispersed particles, and the material has a single denitrification path and poor fault tolerance.
[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing exhaust gas-enhanced solid waste-based building material aggregate, characterized in that, Includes the following steps: 1) Weigh each ingredient according to its weight. 2) Mix 100 parts of steel slag and 50-100 parts of magnesium slag evenly, perform initial grinding, add 2-4 parts of stearic acid or anhydrous ethanol, and finely grind to obtain active micro powder. 3) Add 1-10 parts of biochar to the activated micro powder, mix with water until homogeneous, granulate, and cure to obtain green body granules. 4) The green body particles are placed in a dielectric barrier discharge plasma reactor and subjected to plasma surface treatment in a non-oxidizing atmosphere to obtain purified aggregate. 5) Place the purified aggregate in a container containing CO2-NO2. x It is obtained by treating industrial flue gas.
2. The method for preparing exhaust gas-enhanced solid waste-based building material aggregate according to claim 1, characterized in that, In step 2), the initial grinding is performed by ball milling at 300-500 rpm for 30-60 minutes until D50 ≤ 20μm.
3. The method for preparing exhaust gas-enhanced solid waste-based building material aggregate according to claim 1, characterized in that, Step 2) involves ball milling at 400-700 rpm for 60-180 min, resulting in an active micro powder with a specific surface area of 500-1500 m². 2 / kg.
4. The method for preparing exhaust gas-enhanced solid waste-based building material aggregate according to claim 1, characterized in that, Step 3) The biochar is prepared by anaerobic pyrolysis of biomass raw materials at 300-600℃, with a particle size ≤50μm.
5. The method for preparing exhaust gas-enhanced solid waste-based building material aggregate according to claim 4, characterized in that, The biochar is at least one of corn cob, straw, sawdust, or rice husk.
6. The method for preparing exhaust gas-enhanced solid waste-based building material aggregate according to claim 1, characterized in that, In step 3), the curing process involves hydration curing for 12-48 hours in an environment with a temperature of 60-100℃ and a relative humidity of ≥90%.
7. The method for preparing exhaust gas-enhanced solid waste-based building material aggregate according to claim 1, characterized in that, Step 3) The particle size of the green body is 0.5-10mm.
8. The method for preparing exhaust gas-enhanced solid waste-based building material aggregate according to claim 1, characterized in that, In step 4), the processing power is 100-500 W, the processing time is 5-30 min, the discharge frequency is 5-20 kHz, and the discharge gap is 2-10 mm.
9. The method for preparing exhaust gas-enhanced solid waste-based building material aggregate according to claim 1, characterized in that, Step 4) The non-oxidizing atmosphere is argon, nitrogen, or a mixture thereof.
10. Exhaust gas enhanced solid waste-based building material aggregate, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.